Model Kemitraan Desa dalam Pengelolaan Sampah di Desa Limau Manis, Kecamatan Tanjung Morawa - Siregar, Muhammad Naim; Rahman, Dtm; Pradana, Chandra Anggi; C, Chairina (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The village partnership model in waste management serves as a strategic solution to creating a clean and sustainable environment. This study aims to analyze the implementation of a partnership model involving the village government, community, and private sector in waste management in Limau Manis Village, Tanjung Morawa Subdistrict. The findings reveal that effective collaboration among these three parties enhances community awareness of the importance of waste management, optimizes recycling, and creates economic opportunities through waste processing into value-added products. Through this partnership model, Limau Manis Village has significantly reduced waste volume and contributed to achieving the Sustainable Development Goals (SDGs).